Some considerations on the proposal to decriminalize certain cases of voluntary termination of pregnancy - Alvarado Rojas, Claudio (Derecho Público Iberoamericano, 2014)
This paper analyzes the various facets of debate emerged from the political and legislative proposals seeking the decriminalization of certain cases of abortion. It reviews the terms of the discussion and the context in which it should be developed, the specific cases contemplated in the announcement of Michelle Bachelet and in bill over the matter that are currently pending in Congress, and also the concepts and implications of the so-called therapeutic abortion, abortion in case of rape and fetal non-viability. Finally, other arguments that are usually present in the debate related to these issues are discussed, such as the number of illegal abortions, the penal prosecution of women facing extremely difficult situations, and Chile’s obligations in matter of human rights.